Comparing optimization algorithms for conventional and freeform optical design - Houllier, Thomas; Lépine, Thierry (Optics express, 2019)
Five search algorithms from the literature of black-box optimization were implemented and applied to optical design problems. These algorithms are the Particle Swarm Optimization, Gravity Search Algorithm, Cuckoo Search, Covariance Matrix Adaptation Evolution Strategy and Nelder&Mead Simplex search. The performance of these search algorithms' implementations was assessed using the BBOB2009 (Black Box Optimization Benchmark) benchmark suite. These algorithms were compared in the context of two optical case studies, one with conventional rotationally symmetric optics and one with freeform optics. A comparison was performed against a commercial optical design software. Finally we provided a simple restart scheme applicable in the workflow of an optical designer. To the best of our knowledge, this is the first in-depth quantitative comparison of optimization algorithms for optical design.